1988
DOI: 10.1037/0735-7044.102.6.828
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a complex place task in rats with selective ibotenate lesions of hippocampal formation: Combined lesions of subiculum and entorhinal cortex versus hippocampus.

Abstract: The effects of isolating the hippocampus from its neocortical inputs and outputs by damaging the deep layers of entorhinal cortex and subiculum were compared with direct removal of the hippocampus using acquisition of a complex radial maze task. A series of eight problems (four out of eight arms being correct) were learned under either massed (45 s) or distributed (10 min) practice conditions, thus varying contextual information. Performance of rats with subiculum/entorhinal cortex lesions was similar to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 20 publications
3
46
0
1
Order By: Relevance
“…In contrast, other studies that have performed fiber-sparing lesions of the EC do not report any deficits in the acquisition or retention of these tasks (Bouffard and Jarrard 1988;Pouzet et al 1999;Bannerman et al 2001). Incomplete lesions sparing parts of the EC (Bouffard and Jarrard 1988) or extensive training in other tasks before maze training (Pouzet et al 1999;Bannerman et al 2001), however, have complicated the interpretation of these studies. Furthermore, the absence of a deficit in these pretraining lesion studies may be attributable to compensation by alternative problem-solving strategies.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In contrast, other studies that have performed fiber-sparing lesions of the EC do not report any deficits in the acquisition or retention of these tasks (Bouffard and Jarrard 1988;Pouzet et al 1999;Bannerman et al 2001). Incomplete lesions sparing parts of the EC (Bouffard and Jarrard 1988) or extensive training in other tasks before maze training (Pouzet et al 1999;Bannerman et al 2001), however, have complicated the interpretation of these studies. Furthermore, the absence of a deficit in these pretraining lesion studies may be attributable to compensation by alternative problem-solving strategies.…”
Section: Discussionmentioning
confidence: 44%
“…For example, several studies have reported deficits in the acquisition of water or radial arm maze tasks after lesions of the EC (Olton et al 1978;Holscher and Schmidt 1994;Johnson and Kesner 1994;Cho and Jaffard 1995;Nagahara et al 1995;Galani et al 1997Galani et al , 1998Hardman et al 1997;Ferbinteanu et al 1999;Eijkenboom et al 2000;Oswald and Good 2000). In contrast, other studies that have performed fiber-sparing lesions of the EC do not report any deficits in the acquisition or retention of these tasks (Bouffard and Jarrard 1988;Pouzet et al 1999;Bannerman et al 2001). Incomplete lesions sparing parts of the EC (Bouffard and Jarrard 1988) or extensive training in other tasks before maze training (Pouzet et al 1999;Bannerman et al 2001), however, have complicated the interpretation of these studies.…”
Section: Discussionmentioning
confidence: 92%
“…The opposite pattern of results obtains with certain other memory tasks. Most significant, in spatial learning situations, animals with specific damage to the hippocampus are consistently impaired, whereas-at least under certain conditions-lesions of the rhinal cortex may have little or no effect (e.g., Bouffard & Jarrard, 1988;Holscher & Schmidt, 1994;Jarrard, 1993; but see Liu & Bilkey, 1998;Nagahara, Otto, & Gallagher, 1995). Together, these results indicate that important functional subdivisions exist within the hippocampal system and may be manifest when lesions are restricted to specific subregions of the system (Gaffan & Parker, 1996;Murray, 1996;Myhrer, 1992;Myhrer & Johannesen, 1995).…”
mentioning
confidence: 52%
“…While impaired performance of EC lesioned rats on spatial tasks has been reported in a number of experiments (Schenk and Morris, 1985;Galani et al, 2002;Good and Honey, 1997;Oswald and Good, 2000), we had found earlier that rats with combined damage to EC plus subiculum did not differ from controls in the acquisition of a complex, spatial, radial maze task (Bouffard and Jarrard, 1988). (Reexamination of the histology from this experiment indicates that the presubiculum/parasubiculum in these animals was essentially spared.)…”
Section: Experiments 4: Entorhinal Cortexmentioning
confidence: 83%